814 MCLA-145 (CD137xPD-L1): a potent CD137 agonist and immune checkpoint inhibitor that that does not show signs of peripheral toxicity. (9th November 2020) - Bol, Kees; Marissen, Wilfred; Elaissais-Schaap, Jeroen; Tacken, Paul; Engels, Steef; Wang, Liang-Chuan; Mondal, Arpita; Throsby, Mark; Roberts, Alan; Mayes, Patrick; Geuijen, Cecile
Abstract : Background: Only a fraction of cancer patients benefit from currently available immune checkpoint inhibitors (ICI). Attempts to improve efficacy of ICI by combining with costimulatory receptor agonists such as CD137 (4-1BB) have led to greater anti-tumor activity preclinically but have shown systemic toxicity in the clinic. MCLA-145 is a human CD137xPD-L1 bispecific common light chain antibody (bAb), identified through functional screening of agonist and ICI bAb combinations. Further, MCLA-145 can overcome Treg and macrophage suppression to potently activate T cells in these immune suppressive conditions. In two ICI insensitive xenograft models, MCLA-145 demonstrated good anti-tumor activity and CD8+ T cells were enriched in tumors post treatment (indicative of intratumor expansion and recruitment). No signs of GvHD were observed in mice following treatment with MCLA-145 in contrast to that seen in animals treated with other ICI mAbs. Methods: The EC30 from an in vitro T cell transactivation assay based on IFNg was used as an estimate of the MABEL for MCLA-145. A 2 compartment PK model coupled to a target-mediated drug disposition component was generated based on the available cynomolgus monkey PK data. Results: Repeated doses of MCLA-145 up to 100 mg/kg/wk in cynomolgus monkeys were well tolerated without major adverse effects, and dose-dependent increases in serum MCLA-145 concentrations were observed. Following allometric scaling, the model was used to predict exposure in humans following MCLA-145 IV given over 2-hours every 2 weeks, including the starting dose for the FIH trial. Conclusions: Conditional activation of CD137 signaling by MCLA-145, triggered by a neighboring target cell expressing of PD-L1, may provide both improved efficacy and safety. MCLA-145 is currently undergoing clinical investigation (NCT03922204 ).